Impact of miRNA deregulation on mRNA expression profiles in response to environmental toxicant, nonylphenol - Paul, Saswati; Kim, Seung Jun; Park, Hye-Won; Lee, Seung Yong; An, Yu Ri; Oh, Moon-Ju; Jung, Jin Wook; Ryu, Jae-Chun; Hwang, Seung Yong (KOREAN SOCIETY TOXICOGENOMICS & TOXICOPROTEOMICS-KSTT, 2011)
MicroRNA (miRNA) are approximately 22nt RNA molecules with the ability to regulate gene expression by interacting with its target mRNA. Recent studies demonstrated that miRNA are responsible for determining cell fate and also plays an important role in cellular response to xenobiotics stress and other toxicological phenomenon. Also a number of reports have strengthened the correlation between altered miRNA expression and various cancers. In this study miRNA and mRNA expression profiling was carried out in in-vitro differentiating MCF-7 and HepG2 cell line to understand the effect of nonylphenol (NP), an industrially synthesized environmental toxicant. Analyzing the mRNA- miRNA interaction, we observed correlation between deregulated miRNAs and its predictive differentially expressed target mRNA. We also observed differential expression of two widely studied miRNAs, miR-21 and miR-34 in these cell lines. CTCF is found to be the predictive target of expressed miR-21 in MCF-7. In HepG2 cell line expressed MDM2 is found to be a predictive target of miR-34b. These results support the possible role of miRNA interaction in the expression of its target genes and also ability of environmental toxicant to deregulate miRNA expression.
Keywords: BREAST-CANCER CELLS; HEPATOCELLULAR-CARCINOMA; P53-DEPENDENT APOPTOSIS; MASS-SPECTROMETRY; IN-VIVO; MICRORNA; GENE; P53; TARGET; GROWTH